Identification of the Modifier of Min 2 (Mom2) Locus, a New Mutation That Influences Apc-Induced Intestinal Neoplasia - Silverman, Karen A.; Koratkar, Revati; Siracusa, Linda D.; Buchberg, Arthur M. (Genome Research, 2002)
Min (Multiple intestinalneoplasia) mice carry a dominant mutation in the adenomatous polyposis coli (Apc) gene and develop multiple adenomas throughout their intestinal tract (Moser et al. 1990; Su et al. 1992). Polyp multiplicity in Min mice is greatly influenced by genetic background. A modifier locus, Mom1(Modifier of M in1 ), was identified and localized to distal mouse chromosome 4 (Moser et al. 1992; Dietrich et al. 1993), and accounts for some of the genetic variance in polyp multiplicity. Mom1is a semidominant modifier of polyp size and multiplicity inMin mice (Gould and Dove 1997), and encodes the secretory type II nonpancreatic phospholipase A2 (Pla2g2a) gene (MacPhee et al. 1995; Cormier et al. 1997, 2000). We now report the identification of a second Modifier of M in 2 (Mom2) locus that is the result of a spontaneous mutation. One resistant Mom2 allele can suppress 88%–95% of polyps detected in ApcMin /+ mice, indicating that Mom2 acts in a dominant fashion. Linkage analysis has localized Mom2 to distal mouse chromosome 18. The effects of the Mom2 locus on reducing polyp multiplicity are stronger than the effects of the Mom1 locus, in both the small and large intestines. Some ApcMin /+ mice that carried one resistant Mom2 allele were tumor-free at 21 weeks of age, even in the absence of a resistant Mom1 allele. Thus, the resistant Mom2 allele can, in some cases, completely suppress the penetrance of the ApcMin mutation.
10.1101/gr.206002